Economic Transformation through Agricultural Diversification to Improve Farmers' Welfare: Transformasi Ekonomi Melalui Diversifikasi Pertanian Guna Peningkatan Kesejahteraan Petani - Suprianto Suprianto; Syahfrizka Dyah Nazwa Umbara; Rieko Dita Hermawati (Academia Open, 2025)
General Background: Agricultural transformation plays a critical role in driving economic development, particularly in rural areas. Specific Background: In Indonesia, the agricultural sector remains dominated by monoculture practices, limiting income diversification and resilience among farmers. Knowledge Gap: However, limited studies have examined how agricultural diversification specifically contributes to farmers’ welfare within regional economic development frameworks. Aims: This study aims to analyze the role of agricultural diversification in transforming local economies and improving the welfare of farmers. Results: The findings show that diversification increases productivity, enhances household income stability, and fosters resilience against price and climate shocks. It also supports the growth of rural agro-industries and market accessibility. Novelty: This study uniquely integrates socio-economic indicators with regional development models to demonstrate how diversification directly contributes to sustainable livelihood strategies. Implications: The research implies that policy frameworks should prioritize diversification strategies to achieve inclusive rural development and long-term welfare improvements for agricultural communities. Highlights : Diversification boosts income stability and resilience. It links agriculture with rural industrial growth. Policy support is crucial for sustainable impact. Keywords: Agricultural Diversification, Rural Development, Farmer Welfare, Economic Transformation, Indonesia